Properties of biochar. (1st April 2018) - Weber, Kathrin; Quicker, Peter
Abstract: Biochar can be used in a large number of applications, ranging from heat and power production to soil amendment. The properties of carbonized biomass depend on the feedstock and the process conditions. Selection of suitable conditions to produce a char with the desired properties therefore requires knowledge of dependencies and influencing factors, both quantitatively and qualitatively. This paper reviews and summarizes the results from a large number of experiments on biochar production in order to give a general overview of the properties that can be achieved by feedstock selection and process design. Production processes include both torrefaction as well as slow pyrolysis at high temperatures. The data evaluation has shown that among all process conditions, the treatment temperature has by far the most dominant influence on all properties. Especially the rather narrow temperature range between 200 and 400 °C causes the most significant changes and is therefore very sensible to influences and possibly difficult to control.